A new genus and two new species of Australian Fulviini (Insecta: Heteroptera: Miridae: Cylapinae) - Namyatova, Anna A. (Zootaxa, 2022)
The genus Psallofulvius (Insecta: Heteroptera: Miridae: Cylapinae) and two of its species from Australia, Psallofulvius danbulla and Psallofuvlius dryander, are described as new two science. The diagnoses, descriptions, distribution maps, digital habitus images, SEM images and drawings of male and female genitalia are provided. Although the genus is placed to Fulviini, it also shares some characters with Psallops Usinger which is either placed in the separate subfamily Psallopinae or the tribe Psallopini within the Cylapinae. The key morphological characters and genera presumably related to Psallofulvius are discussed.